Sexual Attitudes and Double Standards: A Literature Review Focusing on Participant Gender and Ethnic Background - Fugère, Madeleine A.; Escoto, Carlos; Cousins, Alita J.; Riggs, Matt L.; Haerich, Paul (Sexuality & Culture : An Interdisciplinary Quarterly, 2008)
We conducted a review of literature regarding sexual attitudes and double standards, focusing on participant gender and ethnic background. We found that men had more permissive sexual attitudes than women, and that African Americans had the most permissive sexual attitudes, followed by White Americans, then by Hispanic Americans and Asian Americans. The literature regarding sexual double standards was mixed; some studies showed evidence of continued sexual double standards and some studies showed the absence of sexual double standards. In some studies, men were more likely to endorse the sexual double standard than women. We found only one article addressing sexual double standards using ethnic background as a quasi-independent variable; this research revealed that non-North American (Russian and Japanese) samples were more likely to endorse the traditional double standard, that sex is more acceptable for men than for women.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; asie; cours; discipline; europe; japon; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; ressource en ligne; russie; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; sexologie; sexualité; systèmes d'oppressions; thématiques; états-unis

Quand les femmes écrivent la guerre : transformation du genre et du monde dans Les hommes qui marchent de Malika Mokeddem et Iran, les rives du sang de Fariba Hachtroudi - Bélanger, Marie-Ève (Université du Québec à Montréal, 2005)
Keywords: 1900-1999; 1990-1999; IREF; afrique; algérie; asie; discipline; guerre; iran; mémoires/thèses; périodes historiques; régions géographiques; thématiques; violences; écriture des femmes*; études littéraires

Quatre mille marches - Chen, Ying (Collection Papiers collés, 2004)
« Romancière avant tout, Ying Chen a tout de même rédigé, au fil des ans, des textes dans lesquels elle tente de réfléchir simplement, modestement, en adoptant le mode de l’interrogation, du souvenir et de la lettre familière plutôt que celui de l’analyse ou de la théorie, à ce que sont pour elle - et peut-être pour ses lecteurs - la portée et la signification de son art, le sens de son itinéraire personnel de femme, d’exilée et d’écrivain, ou la place de la littérature dans le monde éclaté d’aujourd’hui. Il en résulte une série d’essais brefs, écrits dans une prose aussi sobre que directe, qui constituent d’une certaine manière l’accompagnement ou l’écho méditatif de cette parole qui se fait entendre dans ses romans et à travers la voix des personnages auxquels elle a donné vie. »
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; arts; asie; chine; cours; discipline; lit2815; lit3495; point de vue situé; premier cycle; périodes historiques; régions géographiques; thématiques; écriture des femmes*; études littéraires